1994
DOI: 10.1007/bf00018261
|View full text |Cite
|
Sign up to set email alerts
|

Structure-function studies on the interaction of PsaC with the Photosystem 1 heterodimer

Abstract: The interaction of PsaC with the core heterodimer of Photosystem 1 was studied in wild type Synechocystis sp. PCC 6803 and the site-directed mutant R561E of PsaB. The mutant reaction center was much less stable in urea and the functional reconstitution of the mutant core using PsaC was impaired. However, the extent of reconstitution increased in the presence of divalent cations whereas that of the wild type was inhibited. We conclude that the reaction center in the mutant is unstable, most likely due to the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
21
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 24 publications
7
21
0
Order By: Relevance
“…We suggest that coordination of the [4Fe-4S (S-cys)4] cluster into this protein backbone supports the predictions that have been made regarding the organization of the four cysteine ligands for the native Fx cluster in the PS I core (Golbeck, 1993;Rodday et al, 1993Rodday et al, , 1994. However, we also suggest that the specific intercysteinyl sequence we used for modification of loops 1 and 3 of a4, patterned after the Fx domain, is not essential for cluster insertion per se, and possibly two or three connecting glycine residues would suffice.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We suggest that coordination of the [4Fe-4S (S-cys)4] cluster into this protein backbone supports the predictions that have been made regarding the organization of the four cysteine ligands for the native Fx cluster in the PS I core (Golbeck, 1993;Rodday et al, 1993Rodday et al, , 1994. However, we also suggest that the specific intercysteinyl sequence we used for modification of loops 1 and 3 of a4, patterned after the Fx domain, is not essential for cluster insertion per se, and possibly two or three connecting glycine residues would suffice.…”
Section: Discussionsupporting
confidence: 81%
“…The four cysteine ligands for coordination of the Fx cluster reside on two identical interhelical loops, PCDG-PGRGGTC, between helices Vlll and 1X of each PS I core subunit, and we suggested that the loops at the apex of the four-a helix bundle could form a surface-exposed cavity and contribute in the binding of the PsaC subunit (see Figure 1 of Rodday et al, 1993). The working model has been supported experimentally by chemical modification procedures and site-directed mutagenesis of key residues in the Fx loops of the PsaA/PsaB core subunits (Rodday et al, 1993(Rodday et al, , 1994Hallahan et al, 1995) and PsaC Rodday et al, 1996).…”
mentioning
confidence: 99%
“…It is therefore likely that some amino acids of these strands interact with the water-soluble electron acceptors. The mutation of Arg 39 to Gln (R39Q) at the C terminus of the strand ␤C is known to partly inhibit ferredoxin reduction (28), an observation that is corroborated by the structural model. The shortest distance between PsaE and the loop w-x and ␣-helix u (PsaF, PsaJ, and PsaM; see below) are ϳ12 and ϳ20 Å, respectively (Fig.…”
Section: Orientation Of Psae In the Psimentioning
confidence: 86%
“…The intercysteine loops of this motif have been suggested to play a leading role in binding the extrinsic subunit PsaC (39,40). In particular, one of the central arginines of the F X -binding motifs (boldface R in the sequence motif) was postulated to form a salt bridge with an aspartate of PsaC and consequently to be crucial in determining the orientation of this subunit (41).…”
Section: Orientation Of Psae In the Psimentioning
confidence: 99%
“…17 and 19); therefore, the binding activity of the loop must involve interaction with PSI-A and PSI-B. Studies of Rodday et al (36,37) suggest that arginine residues in the conserved domain in PSI-A and PSI-B that binds F X are important for the interaction with PSI-C. The 8-residue internal loop contains two negative charges that may be responsible for the specific interaction with the arginines.…”
Section: Binding Of Psi-c To Photosystem Imentioning
confidence: 99%